The Internet of Elsewhere: The Emergent Effects of a Wired World - Farivar, Cyrus (Rutgers University Press, 2011)
Through the lens of culture,The Internet of Elsewherelooks at the role of the Internet as a catalyst in transforming communications, politics, and economics. Cyrus Farivar explores the Internet's history and effects in four distinct and, to some, surprising societies-Iran, Estonia, South Korea, and Senegal. He profiles Web pioneers in these countries and, at the same time, surveys the environments in which they each work. After all, contends Farivar, despite California's great success in creating the Internet and spawning companies like Apple and Google, in some areas the United States is still years behind other nations. Surprised?You won't be for long as Farivar proves there are reasons that: Skype was invented in Estonia-the same country that developed a digital ID system and e-voting;Iran was the first country in the world to arrest a blogger, in 2003;South Korea is the most wired country on the planet, with faster and less expensive broadband than anywhere in the United States;Senegal may be one of sub-Saharan Africa's best chances for greater Internet access.The Internet of Elsewherebrings forth a new complex and modern understanding of how the Internet spreads globally, with both good and bad effects.